Pembelajaran â€œProjek IPASâ€ Berbasis STEAM sebagai Kajian Implementasi Kurikulum Merdeka di SMK - Muhammad Syaipul Hayat; Sumarno Sumarno; Mahmud Yunus; Noora Qotrun Nada (Jurnal Penelitian Pendidikan IPA, 2023)
The implementation of the Independent Curriculum in SMK requires science learning to be carried out across disciplines through projects. This study aims to examine the potential and implementation of learning "IPAS project" oriented to the STEAM approach as an implementation of the Merdeka curriculum in SMK. The research was conducted using a survey method with a qualitative descriptive approach involving 48 respondents representing 34 out of 163 vocational schools in Central Java. The instrument used is a questionnaire consisting of three open questions about expectations, obstacles and efforts to overcome them; as well as a five-aspect questionnaire on the profile of teachers' understanding of the application of STEAM-based "IPAS Project" learning in the Merdeka curriculum in SMK. Qualitative descriptive analysis is carried out by data reduction, data display, and conclusion drawing. The results showed that although we have understood aspects of the independent curriculum in learning "IPAS Project", there are still obstacles, especially in the application of the STEAM approach. As for the profile of teachers' understanding of the application of STEAM-based "IPAS project" learning in the Merdeka curriculum in SMK, most teachers already have an understanding of the learning concept of "IPAS project" and in its application have involved many students in the implementation of the Merdeka curriculum. But in understanding the concept of STEAM, most teachers still don't master it well. Likewise, in terms of experience in applying the STEAM approach in "IPAS project", not many teachers have applied it in a structured and systematic manner. Based on this, it is recommended that to reduce the gap in expectations and constraints for vocational teachers, an LMS platform is needed to bridge the implementation of STEAM-based "IPAS Project".